Implications of biodiesel-induced land-use changes for CO2 emissions: case studies in Tropical America, Africa, and Southeast Asia - Achten, W.M.J.; Verchot, Louis V. (2011)
Biofuels are receiving growing negative attention. Direct and/or indirect land-use changes that result from their cultivation can cause emissions due to carbon losses in soils and biomass and could negate any eventual greenhouse gas (GHG) reduction benefit. This paper evaluates the implications of land-use change emission on the climate-change mitigation potential of different biofuel production systems in 12 case studies in six countries. We calculated carbon debts created by conversion of different land-use types, ranging from annual cropland to primary forest. We evaluated case studies using three different biofuel crops: oil palm, Jatropha, and soybean. The time needed for each biofuel production system to pay back its carbon debt was calculated based on a life-cycle assessment of the GHG reduction potentials of the system. Carbon debts range from 39 to 1743.7 Mg C02 ha-1. The oil palm case studies created the largest carbon debts (472.8–1743.7 t C02 ha-1) because most of the area expansion came at the expense of dense tropical forest. The highest debt was associated with plantation on peatland. For all cases evaluated, only soybean in Guarantã do Norte and Alta Floresta, Brazil needed less than one human generation (30 years) to repay the initial carbon debt. Highest repayment times were found for Jatropha (76–310 years) and oil palm (59–220 years) case studies. Oil palm established in peatlands had the greatest repayment times (206–220 years). High repayment times for Jatropha resulted from the combined effects of land-cover change and low CO2 emission reduction rate. These outcomes raise serious questions about the sustainability of biofuel production. The carbon implications of conversion of (semi-) natural systems with medium to high biomass indicate that, in order to generate climate benefits, cultivation of biofuel feedstocks should be restricted to areas that already have low carbon content.